CONVERSION OF PROPANE-PROPYLENE FRACTION INTO AROMATIC HYDROCARBONS ON MODIFIED ZEOLITE CATALYSTS - B.T. Tuktin; A.M. Temirova; G.T. Saidilda; A.A. Omarova (Academic Scientific Journal of Chemistry, 2020)
The process of transformation of propane-propylene fraction into aromatic hydrocarbons on zeolitecontaining catalysts modified Zn, La, Cr, Zr and P was discovered. The process was carried out in an installation in a flow installation at atmospheric pressure with a temperature variation from 350 to 600°C and a volumetric feed rate of 150-1020 h-1. The catalysts were prepared by impregnation of aluminum hydroxide and zeolite ZSM-5 with aqueous solutions of nitric acid salts of metals and phosphoric acid. The physical and chemical characteristics of the developed catalysts are studied. The BET method established that the surface of the developed catalysts fluctuates within 211.0-274.0 m2 / g of the catalyst. Catalysts are predominantly mesoporous: pores with d ≈ 2.0-3.0 nm predominate. It is shown that the developed modified zeolite-containing catalysts have high catalytic activity and selectivity in the process of processing the propane-propylene fraction into aromatic hydrocarbons. The predominant products formed during the processing of C2-C4 alkanes are toluene and benzene. It was found that the highest yield of aromatic hydrocarbons is 52.8% (550°С, 150 h-1) on the catalyst Zn-La-Р-Cr-ZSM-Al2O3 with a conversion rate of 100.0%, selectivity for aromatic compounds - 52.8%. Modified zeolite-containing catalysts have multifunctional properties. The composition of liquefied petroleum gas processing products shows that the formation of aromatic hydrocarbons occurs in one stage as a result of cracking, dehydrogenation, oligomerization, dehydrocyclization, alkylation reactions